Facial attractiveness: General patterns of facial preferences - Kościński, Krzysztof (Anthropological Review, 2007)
This review covers universal patterns in facial preferences. Facial attractiveness has fascinated thinkers since antiquity, but has been the subject of intense scientific study for only the last quarter of a century. Many facial features contribute to facial attractiveness: Averageness and symmetry are preferred by males and females, probably because they signal genetic quality and developmental stability. Men prefer highly feminized female faces because they reflect high estrogen levels and low testosterone levels. This indicates that the woman is reproductively healthy. Women, on the other hand, prefer a moderate level of male facial masculinity, since facial masculinity that is too pronounced signals high level of testosterone and, thereby, a poorly developed pro-family personality. In women, facial hair is detrimental to facial attractiveness. In men, the effect is not consistent. Faces with a clear complexion are attractive to both men and women. Men prefer light and smooth skin in women. Positive facial expressions also enhance facial attractiveness. Many factors, in particular skin condition and facial proportions, affect perceived age, which is an important component of facial attractiveness. Men in particular strongly prefer youthful-looking female faces. Facial preferences enable an individual to recognize reproductively fit mates. Therefore, facial preferences are adaptive, although non-adaptive mechanisms related to general brain function also play a role.